Acute leukaemia during azathioprine therapy. Issue 617 (March 1977) - Gilmore, I. T.; Holden, G.; Rodan, K. S.
Abstract : Various tumours, in particular lymphomas, have been reported in association with azathioprine treatment, both after renal transplantation and in other conditions. A case is reported here of acute myeloid leukaemia associated with azathioprine therapy for rheumatoid arthritis, and this is now the third case reported in the world literature of leukaemia arising during azathioprine therapy for a non-malignant condition.